Differing intrinsic biological properties between forebrain and spinal oligodendroglial lineage cells - Horiuchi, Makoto (J Neurochem, 2017)
Differentiation of oligodendroglial progenitor cells (OPCs) into myelinating oligodendrocytes is known to be regulated by the microenvironment where they differentiate. However, current research has not verified whether or not oligodendroglial lineage cells (OLCs) derived from different anatomical regions of the central nervous system (CNS) respond to microenvironmental cues in the same manner. Here, we isolated pure OPCs from rat neonatal forebrain (FB) and spinal cord (SC) and compared their phenotypes in the same in vitro conditions. We found that although FB and SC OLCs responded differently to the same external factors; they responded differently to proliferation to mitogens, oligodendrocyte phenotype after differentiation, and cytotoxic responses to α-amino-3-hydroxy-5-methyl-4-isoxazolepropionate-type glutamate receptor-mediated excitotoxicity at immature stages of differentiation in a cell-intrinsic manner. Moreover, transcriptome analysis identified genes differentially expressed between these OPC populations, including those encoding transcription factors (TFs), cell surface molecules, and signaling molecules. Particularly, FB and SC OPCs retained the expression of FB- or SC-specific TFs, such as Foxg1 and Hoxc8, respectively, even after serial passaging in vitro. Given the essential role of these TFs in the regional identities of CNS cells along the rostrocaudal axis, our results suggest that CNS region-specific gene regulation by these TFs may cause cell-intrinsic differences in cellular responses between FB and SC OLCs to extracellular molecules. Further understanding of the regional differences among OPC populations will help to improve treatments for demyelination in different CNS regions and to facilitate the development of stem cell-derived OPCs for cell transplantation therapies for demyelination.